Impact of Remitances on Reserves (Global Journal of Management and Business Research, 2012)
The study focused on the importance of remittances and reserves and also sees its implication for reserve increasing in three countries (Pakistan, India and Bangladesh). We analysis the impact of remittances on reserves in these three countries for the period 2000-2009.The regression analysis shows that remittances effect on reserves positively and significantly. Furthermore the study also finds that remittances have a strong and statistically significant impact on reserve increasing thus the reserves will increase when remittances will increase. The study also finds country wise analysis, Indian country is on top with respect to remittances and reserves and the Indian reserves are heavily dependent on remittances.
Keywords: Remittances; Reserves; Pakistan; India; Bangladesh